Spiritual Therapy On Anxiety Levels In Preoperative Patients: A Literature Review - Kaimudin, La Ode Idris; Lisum, Kristina (LPPM Universitas Pekalongan, 2025)
ABSTRACT Background: Surgery is part of an invasive medical procedure that involves opening or injuring a part of the body, which then ends with the process of closing or suturing the wound. This procedure often causes anxiety for patients who are about to undergo surgery. According to Malaha et.al 2021) Reactions that arise in patients are in the form of psychological and physiological stress, but the most commonly experienced are psychological reactions such as anxiety. Pre-operative anxiety is often experienced by patients because they feel they are threatened. There are several nursing care provided to patients who will undergo surgery, including Spiritual therapy in the form of spiritual guidance. Research Method: Writing literature reviews uses a narrative review approach by analyzing and interpreting the results of the research. The secondary data used was collected from Google Scholar and PubMed. The search for journals in this study was carried out from December 7, 2024 to 2025 in February Research Results: The results of the literature review explained from six journals, all of which concluded that there was a significant influence related to the spiritual therapy given to patients. From the results of the review, researchers can conclude that there is a meaningful difference between